Ethnobotanical Study of Medicinal Plants in Traditional Medicine of The Karo Tribe Based on Local Wisdom - Wina Dyah Puspita Sari; Sanimah; Cicik Suriani; Aswarina Nasution (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to uncover the taxonomy of medicinal plants and ethnobotanical aspects in the traditional medicine of the Karo tribe in North Sumatra. The study was carried out in a qualitative descriptive manner with an ethnobotanical approach through direct observation, in-depth interviews, and documentation of the use of medicinal plants by the local community. The results show that there are 78 species of medicinal plants belonging to 26 families, with the highest dominance in the Zingiberaceae family. The most commonly used parts of plants are leaves (55%) and rhizomes (25%). These plants are used in various herbs such as Karo oil, param, spray, and traditional herbal medicine. Processing processes such as refining, boiling with coconut oil, and drying reflect a local understanding of the principles of extraction and synergy of active ingredients. This study shows that the local knowledge of the Karo people is closely related to scientific principles and has great potential to be developed in contextual science education and biodiversity conservation.